A HD-Zip I transcription factor from physic nut, JcHDZ21, confers sensitive to salinity in transgenic Arabidopsis - Tang, Yuehui; Peng, Jingrui; Lin, Jin; Zhang, Miaomiao; Tian, Yun; Shang, Yaqian; Chen, Shuying; Bao, Xinxin; Wang, Qiyuan (Frontiers in Plant Science, 2023)
HD-Zip is a plant-specific transcription factor that plays an important regulatory role in plant growth and stress response. However, there have been few reports on the functions of members of the physic nut HD-Zip gene family. In this study, we cloned a HD-Zip I family gene from physic nut by RT-PCR, and named JcHDZ21. Expression pattern analysis showed that JcHDZ21 gene had the highest expression in physic nut seeds, and salt stress inhibited the expression of JcHDZ21 gene. Subcellular localization and transcriptional activity analysis showed that JcHDZ21 protein is localized in the nucleus and has transcriptional activation activity. Salt stress results indicated that JcHDZ21 transgenic plants were smaller and had more severe leaf yellowing compared to those of the wild type. Physiological indicators showed that transgenic plants had higher electrical conductivity and MDA content, and lower proline and betaine content compared with wild-type plants under salt stress. In addition, the expression of abiotic stress-related genes in JcHDZ21 transgenic plants was significantly lower than that in wild type under salt stress. Our results showed that ectopic expression of JcHDZ21 increased the sensitivity of transgenic Arabidopsis to salt stress. This study provides a theoretical basis for the future application of JcHDZ21 gene in the breeding of physic nut stress-tolerant varieties.